Metodología canvas como estrategia pedagógica emprendimiento y gestión - Rosalba Verónica, Paredes Veintimilla (2021)
ABSTRACT The aim of the present research work is to determine the contribution of the pedagogical strategy through the Canvas methodology in the teaching-learning process of the Entrepreneurship and Management subject. The research problem is given, the students of the third year at Sultana de los Andes School in Cumandá, do not have a pedagogical strategy that helps to prepare them for the creation of new educative ventures. The methodological design has a quantitative and qualitative data and analyses both together. It is a field bibliographic, and non-experimental research. The research level begins as exploratory and then the descriptive, correlational and explanatory meths. The applied technique was the survey, carried out in Google Forms and version 21 of the SPSS tool was used to analyze its reliability, through Cronbach's Alpha. The population is made up of the total number of students from the "Sultana de los Andes" Educational Unit and non-probability sampling was used of the third year high school students. This research confirms the hypothesis that the pedagogical strategy through the Canvas methodology contributes to improving the teaching-learning process of the Entrepreneurship and Management subject. KEYWORDS Canvas methodology, pedagogical strategy, entrepreneurship and management; ICTs in education DORIS Firmado digitalmente por DORIS ELIZABETH VALLE VINUEZA VALLE VINUEZA Fecha: 2021.11.17 12:37:54 -05'00' Reviewed by: Mgs. Doris Valle V. ENGLISH PROFESSOR C.C 0602019697